Qualitative analysis of parents' experience with early detection of hearing loss. Issue 4 (19th March 2004) - Russ, S A; Kuo, A A; Poulakis, Z; Barker, M; Rickards, F; Saunders, K; Jarman, F C; Wake, M; Oberklaid, F
Abstract : Aims: To determine key themes from parents' comments on paths to diagnosis and intervention for their children with hearing loss, following introduction of at-risk neonatal hearing screening and modification of distraction test screening for infants not at-risk. Methods: Parents of children born in 1993 in Victoria, Australia, who were eligible for screening via the Victorian Infant Hearing Screening Program and who were subsequently diagnosed with a permanent congenital hearing loss and fitted with hearing aids prior to the year 2000 were asked to complete a semi-structured questionnaire shortly after aid fitting. Two researchers independently analysed parent comments using the constant comparative method. Results: Parents of 82 children (61%) replied to the questionnaire. Themes analysis revealed a generally positive response to neonatal ABR screening, with a mixed response to the distraction test; powerful emotions experienced by parents at diagnosis including denial and shock; frustration arising from delays in diagnosis, and communication difficulties with providers. Special difficulties testing children with other medical and developmental problems, confusion about tympanostomy tube insertion, and difficulty with wearing hearing aids were also reported. Some children had experienced problems in the school setting. Experience of post-diagnostic services was generally positive. Conclusions: Parents need greater support both during the testing of screen failures and at the time of diagnosis. Providers need more training in how to communicate findings to parents, particularly at times when parents are experiencing strong emotions. Parents need more strategies to enable hearing aid wearing in very young children. Some children with additional medical, developmental, and behavioural problems need specialised approaches to testing.